SELF-EFFICACY AS A MODERATOR IN THE INFLUENCE OF SOCIAL MEDIA INFLUENCER, INVESTMENT KNOWLEDGE, INVESTMENT RETURN, AND POCKET MONEY ON GEN Z'S INVESTMENT INTEREST: EVIDENCE FROM MALANG, INDONESIA - Miladina, Alya Farhan; Permatasari, Ditya (Jurnal Akuntansi Bisnis, 2025)
Background: The city’s status as an educational hub with a large student population makes Gen Z in Malang more exposed to social media trends and financial information, which further stimulates their enthusiasm for investment. However, this interest is not always accompanied by sufficient investment knowledge, financial literacy, or confidence, leading to a gap between intention and behavior. Factors such as the influence of social media influencers, investment knowledge, expected returns, and pocket money are believed to shape this investment interest, while self-efficacy plays a crucial moderating role in determining whether these factors can effectively strengthen Gen Z’s investment intentions in Malang.Objective: This study aims to examine Generation Z’s investment interest in Malang City, an educational hub that attracts students from across Indonesia. Malang’s unique blend of academic and urban life provides a distinct context compared to metropolitan areas such as Jakarta or Surabaya, making it an ideal setting to analyze variations in Gen Z’s investment behavior.Research Methods: This study employed a quantitative design with purposive sampling, resulting 232 respondents. The data were obtained through online questionnaires shared via social media and analyzed using Partial Least Squares (PLS) with SmartPLS version 4.1.1.Research Results: The results show that social media influencers and investment returns significantly increase investment interest, while investment knowledge and pocket money do not. The results show that self-efficacy significantly moderates the effect of social media influencers, investment knowledge, and investment returns on investment interest, while it does not significantly moderate the effect of pocket money.Originality/Novelty of Research: This study contributes to the literature by examining self-efficacy as a moderating factor between key determinants and investment interest, specifically targeting Generation Z in Malang City.